Metastatic Breast Cancer: Cytology Diagnosis with Implications for Treatment - Alaa Hrizat; Elena Brachtel (MDPI AG, 2022)
Breast cancer is among the most frequent malignancies in women worldwide. While early detection and effective treatment provide many women with a cure and prevent their cancer from spreading, metastases to distant sites still occur in around 20% of women suffering from breast cancer. These relapses occur in many forms and locations and are as varied as the primary breast tumors. Metastatic spread makes a cancer incurable and potentially lethal, but new, targeted treatments can offer control of the cancer cells if the features of new targets are unlocked by advanced diagnostic testing. The article offers an overview of the pathomechanisms of metastatic progression and describes the types of metastases, such as hormone-receptor-positive and -negative breast cancers, and HER2-overexpressing or triple-negative types. Once distant metastatic spread occurs, cytology allows a precise diagnosis to confirm the breast origin. Other molecular targets include ESR1 and PIK3CA mutations, MSI, NTRK fusion, PD-L1 expression and others, which can be obtained also from cytology material and used to determine eligibility for emerging targeted therapeutic options. We outline the diagnostic features of metastatic breast cancer in cytology samples, together with validated and emergent biomarkers that may provide new, targeted treatment options.